Purification strategy and effect of impurities on corrosivity of dehydrated carnallite for thermal solar applications. Issue 71 (16th December 2019) - Zhao, Youyang; Klammer, Noah; Vidal, Judith
Abstract : Thermal and chemical purifications empower molten chlorides for next generation concentrating solar power (CSP) applications. Abstract : This paper presents a purification method for dehydrated carnallite (DC)—a commercial ternary MgCl2 –KCl–NaCl salt—for concentrating solar power (CSP) applications based on a thermal and chemical treatment using the reduction power of Mg. The purification is effective at reducing MgOH + by an order of magnitude—from around 5 wt% in non-treated salt to less than 0.5 wt% in post-purification salt. The corresponding decrease in the measured corrosion rate of Haynes 230 at 800 °C from >3200 μm per year to around 40 μm per year indicates that soluble MgOH + is indeed correlated to corrosion. The addition of elemental Mg serves as both a scavenger of impurities and corrosion potential control, which are considered the primary mechanisms for corrosion mitigation.